Modelling of SFRC using inverse finite element analysis - Tlemat, H.; Pilakoutas, Kypros; Neocleous, Kyriacos (My University, 2006)
A method of inverse finite element analysis is used to determine the constitutive relationship of SFRC in tension, using primary experimental data. Based on beam bending test results and results from pull-out tests, an attempt is made to explain the physical processes taking place during the cracking stage. Basic models predicting the behaviour of SFRC in tension are proposed. © RILEM 2006.
Keywords: Steel fibers; Fiber reinforced materials; Fiber-reinforced concrete